Design and Analysis for the presence of Bacillus cereus in blood using Plasmons - S S, Ajey; C Srikanth, P; D N Nagalaxmi, Dr.; V R Krishnamurthy, Dr.; Chandra Shekar, N. (International Journal of Engineering and Technology, 2018)
The Photonic Waveguide biosensors are used for detection and analysis of bio-analyte. These photonic waveguides use Plasmon vibrations technique for detection of the analyte by combining biological components with physicochemical detector. FDTD which stands for finite difference time domain is used for designing a 2- D Surface Plasmonic Resonance based photonic waveguide-based biosensor for detection of the Micro-bacteria named Bacillus cereus in order to find the toxicity in the blood. For modelling and designing the photonic waveguide sensor, Rsoft CAD simulation tool is used. Monitor values, wavelength and Frequency spectrums have been observed and by using these parameters Sensitivity is calculated. A slight variation in the refractive index leads to a substantial change in the frequency which can be seen in the band structure, therefore the designed structure behaves as sensor. Therefore, designed sensor is greatly sensitive to the modifications in RI and hence it discriminates among the dissimilar constituents of the analyte. Â Â